Seasonal variations and source estimation of saccharides in atmospheric particulate matter in Beijing, China. (May 2016) - Liang, Linlin; Engling, Guenter; Du, Zhenyu; Cheng, Yuan; Duan, Fengkui; Liu, Xuyan; He, Kebin
Abstract: Saccharides are important constituents of atmospheric particulate matter (PM). In order to better understand the sources and seasonal variations of saccharides in aerosols in Beijing, China, saccharide composition was measured in ambient PM samples collected at an urban site in Beijing. The highest concentrations of total saccharides in Beijing were observed in autumn, while an episode with abnormal high total saccharide levels was observed from 15 to 23 June, 2011, due to extensive agricultural residue burning in northern China during the wheat harvest season. Compared to the other two categories of saccharides, sugars and sugar alcohols, anhydrosugars were the predominant saccharide group, indicating that biomass burning contributions to Beijing urban aerosol were significant. Ambient sugar and sugar alcohol levels in summer and autumn were higher than those in spring and winter, while they were more abundant in PM2.5 during winter time. Levoglucosan was the most abundant saccharide compound in both PM2.5 and PM10, the annual contributions of which to total measured saccharides in PM2.5 and PM10 were 61.5% and 54.1%, respectively. To further investigate the sources of the saccharides in ambient aerosols in Beijing, the PM10 datasets were subjected to positive matrix factorization (PMF) analysis. Based on the objective function to be minimized and the interpretable factors identified by PMF, six factors appeared to be optimal as to the probable origin of saccharides in the atmosphere in Beijing, including biomass burning, soil or dust, isoprene SOA and the direct release of airborne fungal spores and pollen. Graphical abstract: Highlights: Total measured saccharide concentrations in PM2.5 and PM10 were higher than most of those observed around the world. The ratio of levoglucosan to mannosan was higher during the harvest season. Ambient sugars and sugar alcohols were more abundant in fine mode (PM2.5 ) during winter. Saccharides in Beijing aerosol can be derived from biomass burning, suspended soil, isoprene SOA, fungal spores and pollen.